Developing a high-quality patient-centric integrated model for emergency care system in selected districts of India: An implementation research protocol (INDIA-EMS Study) - Manu Ayyan S; Arvind Kumar Singh; Hemantkumar S. Patadia; Shreyas Patel; Saurabh Saigal; Jeyaraj Durai Pandian; Thejus Varghese; Ankur Joshi; Meenakshi Sharma (PLoS ONE, 2025)
Introduction Integrated emergency care systems are essential for achieving universal health coverage and managing time-sensitive conditions. In India, emergency care remains fragmented, with limited resources and coordination across healthcare tiers. The INDIA-EMS study aims to develop and evaluate a patient-centric, high-quality integrated emergency care model in diverse Indian districts. Methodology The proposed implementation research is designed as a mixed methods study to be conducted over a 3-year period in selected districts of the states of Punjab, Gujarat, Madhya Pradesh, Odisha and Puducherry. The public/private medical college hospital/ tertiary care hospital in the district will serve as a hub and primary health care services as spokes. The health facilities will be graded according to the availability of resources for their readiness and preparedness to provide care for handling a particular emergency condition. The steps to build and implement the model are: 1. a gap analysis related to emergency care at both pre-hospital and health facility level; 2. a community-based survey in a sample of 30,000 in 5 districts for EMD burden estimates and health-seeking behaviour at baseline and endline; 3. use a consolidated framework for implementation research to develop, optimise and implement hub and spoke model through three cycles of iterative processes; and; 4.evaluation for feasibility, acceptability, cost, effectiveness and coverage. Discussion A high-quality patient-centric integrated emergency care model may be able to ensure efficient delivery of care to patients experiencing time-sensitive emergencies and advance towards the coveted target under Sustainable Development Goals (SDGs). Ethics and dissemination Ethics approval was obtained in all the project sites. The results of the project will be submitted to a peer-reviewed journal for publication, in addition to national and state-level dissemination. Trial registration The trial is registered with CTRI (Clinical Trial Registry of India; CTRI/2024/01/061304).